Quadruple Helix Collaboration In Developing A Village Creativity And Innovation Policy Model - Dwi Nanda Cahya Yuliani; Rizky Nurhidayat Perdana (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Quadruple helix collaboration synergy is an essential pillar in the formulation of the Village Creativity and Innovation Policy Model. Based on the understanding that the government faces limited resources and scope of authority in policymaking, this study examines the roles of stakeholders in the quadruple helix collaboration between the Center for Village and Disadvantaged Region Competitiveness Development (BPI) of the Ministry of Villages, Development of Disadvantaged Regions (Kemendes PDT RI), Gadjah Mada University, Gedhe Nusantara University, and village communities in developing these policy recommendations. The method used in writing this journal article is a qualitative approach with descriptive methods to understand the conditions of a natural object. This study aims to examine the roles of stakeholders in the quadruple helix collaboration in developing policy recommendations, namely the Village Creativity and Innovation Policy Model. Data collection techniques were through observation and semi-formal interviews. The subject of this study is the role of the stakeholders involved, while the object of research is the quadruple helix collaboration, focusing on the roles and involvement of stakeholders.